SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP ACTIVITIES SOCIO-PHILOSOPHICAL ANALYSIS - Shamsiddinov Burkhanjon Jakbarovich; Khudoyberganov Sharifjon Shokiraliyevych (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This social-philosophical analysis explores the implications and underlying principles of small business and private entrepreneurship. It delves into the societal and philosophical aspects of these activities, examining their impact on individuals, communities, and the broader economy.The analysis begins by highlighting the motivations behind small business and private entrepreneurship, emphasizing the desire for autonomy, self-determination, and personal fulfillment. It explores how these activities reflect fundamental aspects of human nature and the pursuit of independence. Overall, this social-philosophical analysis highlights the importance of small business and private entrepreneurship in society. It recognizes their positive contributions to economic development and personal fulfillment while addressing the challenges and ethical considerations associated with these activities. By striking a balance between individualism and societal well-being, societies can harness the full potential of small businesses and private entrepreneurship for the benefit of all.